Complete chloroplast genome of Disporum sessile - Park, Inkyu (Mitochondrial DNA B Resour, 2019)
Disporum sessile roots are used as a medicinal herb. To ensure the accurate identification of D. sessile, we sequenced its chloroplast genome using the Illumina MiSeq platform. Results showed that the chloroplast genome of D. sessile is 159,102 bp in size, with a large single-copy (LSC) region (85,456 bp), a small single-copy (SSC) region (17,108 bp), and two inverted repeat (IR) regions (IRa and IRb; 28,269 bp each). Additionally, the chloroplast genome contains 112 unique genes, including 78 protein-coding, four ribosomal RNA, and 30 transfer RNA genes. Phylogenetic analysis revealed that D. sessile is most closely related to Colchicum autumnale.